(untitled) (Yosh olimlar, 2026)
This article discusses the formation of educational infrastructure through the integration of digital technologies and modern teaching methods in technological education. It analyzes the effective use of information and communication technologies (ICT), interactive teaching approaches, project-based learning, and opportunities for fostering students’ independent and creative thinking. The importance of creating a comprehensive digital learning environment and enhancing the overall quality of education is also emphasized. The article highlights future prospects for developing a modern, technology-driven educational system.